(untitled) (Strathmore Law Review, 2022)
Extradition encompasses both the administrative bodies and the judicial bodies. The Extradition (Contiguous and Foreign Countries) Act requires that an authority to proceed is issued once the Attorney General receives the extradition request. This is different from what is contained under the 2010 Constitution. Currently, the 2010 Constitution mandates the Director of Public Prosecutions to institute criminal proceedings as opposed to the Repealed Constitution which conferred it on the Attorney General. Hence, courts have interpreted the authority to proceed in extradition to fall within different ambits. For example, in the 2015 case of Samuel Gichuru v Attorney General, the High Court held that this authority fell under the Office of the Director of Public Prosecutions. This was overturned in the 2018 Court of Appeal case, Chrysanthus Okemo v Attorney General, where the authority was to be granted by the Attorney General. However, the Supreme Court in Director of Public Prosecutions v Chrysanthus Okemo (2021) upheld the High Court’s decision. Therefore, this paper sets out to determine and streamline the nature of extradition in Kenya, given that there exist overlapping mandates and lacunae that the law needs to address for a uniform practice of extradition in Kenya.